2009
DOI: 10.3109/00016480902798343
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck cancer in young people: a series of 52 SCCs of the oral tongue in patients aged 35 years or less

Abstract: The WHO performance status was excellent for all patients. Thirty-seven were classified as T1-T2 and 38 were N0. All of them except one were treated with curative intent. Treatment failures were observed in 25 patients (48%). Four patients could be successfully salvaged after SCCOT recurrence or progression. The disease-free survival (DFS) was 52% at 5 years. The 5-year overall survival (OS) rate was 64%. Factors that affected the OS were invasion of the floor (p=0.009), cross over of the midline (p=0.02), pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
2
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 19 publications
1
19
2
3
Order By: Relevance
“…Five of the 10 papers about the tumor-node-metastasis (TNM) Staging System indicated that a large amount of patients were diagnosed as T1 and/or T2 (8,(13)(14)(15)20) , being stages T3 and T4 (extensive tumors) predominant in other works (7,(10)(11)(12)18) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five of the 10 papers about the tumor-node-metastasis (TNM) Staging System indicated that a large amount of patients were diagnosed as T1 and/or T2 (8,(13)(14)(15)20) , being stages T3 and T4 (extensive tumors) predominant in other works (7,(10)(11)(12)18) .…”
Section: Resultsmentioning
confidence: 99%
“…As for sample size, the number of participants ranged from 10 to 2,223 young subjects, as described in Table 1. Age distribution of patients varied: individuals considered young were those aged 18-39 years (7,8,10,11) (23.5%), < 30 years (13,20) (3,6,8,9,(11)(12)(13)(14)(16)(17)(18)(19)(20)(21) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence rate of HNSCC has reached 0.4-3.6% in patients younger than 40 years which has drawn physicians' attention to the changing face of the disease (Llewellyn et al, 2001). On the other hand, recent studies have revealed differences of the risk factors and prognosis of HNSCC, in patients younger than 40 and the older patients, although controversy still exists regarding disease outcomes in young and old patients: some authors report a worse prognosis of the disease in the young compared to the old (Mallet et al, 2009;Kaminagakura et al, 2010;Soudry et al, 2010;Bachar et al, 2011;Kostrzewska-Poczekaj et al, 2012) while other studies have not found a significant clinical difference, or even a more favorable prognosis in younger patients (Luna-Ortiz et al, 2011). In fact, even if the tumors are histologically more mature and less malignant in younger patients compared to older ones, they are usually more advanced clinically at the time of diagnosis due to late referral of young patients to physicians (Shiboski et al, 2005;Sink et al, 2011).…”
Section: Introductionmentioning
confidence: 99%